1998
DOI: 10.1136/aim.16.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acupuncture in Dentistry: A Systematic Review

Abstract: SummaryPublished controlled studies on the analgesic effect ot' acupuncturc in dentistry arc still relatively few, but those which lulfil predefined nethodological critetia are rcvlewed to assess if acupuncture is effective in this field. A literature search identifiecl 74 papers published between 1966 and 1996, and 18 are reviewed. Only l5 of the papers fulfil a number of predefined criteria: having a reterence Eroup t rndomi\dlion. blindtng -Jpptoptiate \tati5ti \ \urfi, ient follou up. etc. Ol lhe !5 pdpet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Of the 65 systematic reviews including studies in the field of dentistry, 20 (31%) focused on pain (Table 2). Only three of these reviews focused on dental pain alone (13–15), the remainder of the reviews pooled studies set in both dental and medical settings. The other areas most frequently evaluated within the systematic reviews were periodontics, caries, oral medicine, and oral maxillofacial surgery.…”
Section: Areas Of Dentistry Covered By the Systematic Reviewsmentioning
confidence: 99%
“…Of the 65 systematic reviews including studies in the field of dentistry, 20 (31%) focused on pain (Table 2). Only three of these reviews focused on dental pain alone (13–15), the remainder of the reviews pooled studies set in both dental and medical settings. The other areas most frequently evaluated within the systematic reviews were periodontics, caries, oral medicine, and oral maxillofacial surgery.…”
Section: Areas Of Dentistry Covered By the Systematic Reviewsmentioning
confidence: 99%
“…They suggest that the mechanical action of needling causes receptors to send neural impulses to the spinal cord to act on ascending pathways to the brain and cause the release of neurotransmitters that subsequently modulate pain processing in the brain. This alternative theory of the mechanism of acupuncture is based on studies that have used acupuncture to treat head and neck pain 19–28 . It has also been suggested that acupuncture‐induced analgesia is mediated by the release of endogenous opioids 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of papers on the use of acupuncture in dentistry published between 1966 and 1996 showed standard acupuncture to be more effective than a placebo or sham acupuncture. As per the study, it was concluded that acupuncture should be considered a reasonable alternative or supplement to current dental practice as an analgesic [22].…”
Section: An Overview On Alternative Methodsmentioning
confidence: 97%